The interpretation of Kenosis from Origen to Cyril of Alexandria: dimensions of self-emptying in the reception of Philippians 2:7 - Magree, Michael C. (Oxford Early Christian Studies, 2024)
The self-emptying of Christ, proclaimed in the letter to the Philippians 2:7, remains a much-debated topic in modern theology and exegesis. This book brings the insights of Greek Christianity to the understanding of kenosis to illustrate that new dimensions of the topic open up when it is examined in the historical era of early Christianity.